Response - Parks, Rachel B.; Brooks, M. Alison (Medicine & Science in Sports & Exercise, 2017)
Response of the authors to the letter to the editor (Chapman RF, Sinex J, Wilber R, et al. Routine screening for iron deficiency is an important component of athlete care. Med Sci Sports Exerc. 2017;49(11):2364) concerning Parks RB, Hetzel SJ, Brooks MA. Iron deficiency and anemia among collegiate athletes: a retrospective chart review. Med Sci Sports Exerc. 2017;49(8):1711-5